Efficacy of Cooperative Learning Strategy on the Mathematics Performance of Senior Secondary School Students in Sokoto State - ABDULLAHI, Umar; ADAMU, Ibrahim; SIRAJO, Musa (Ilorin Journal of Education, 2023)
This study was carried out to find out the efficacy of the cooperative learning strategy on the mathematics performance of senior secondary school students in Sokoto State, Nigeria. A quasi-experimental design was adopted, which consists of two groups: the control group and the experimental group. Three objectives, three research questions, and their corresponding null hypotheses were precisely addressed in the study. Three schools were chosen at random for the study and its population, which includes all senior secondary school II (SSS II) students in Sokoto, 240 of whom were chosen through intact classes as samples from the three schools under study for both the experimental and control groups. The instrument used for data collection was the "Mathematics Integration Performance Test" (MIPT), which consists of 24 items and was validated by three (3) experts and has a reliability coefficient of 0.88. Based on the findings of the study, cooperative learning strategies have significant benefits for secondary school mathematics teaching and learning. It was then recommended that the cooperative learning strategy be adopted as the most effective method and pedagogy of mathematics instruction since the result of the study shows that cooperative learning helps students learn mathematics and improves their performance in school.